2013
DOI: 10.3390/ijms14024298
|View full text |Cite
|
Sign up to set email alerts
|

The Increasing Complexity of the Oncofetal H19 Gene Locus: Functional Dissection and Therapeutic Intervention

Abstract: The field of the long non-coding RNA (lncRNA) is advancing rapidly. Currently, it is one of the most popular fields in the biological and medical sciences. It is becoming increasingly obvious that the majority of the human transcriptome has little or no-protein coding capacity. Historically, H19 was the first imprinted non-coding RNA (ncRNA) transcript identified, and the H19/IGF2 locus has served as a paradigm for the study of genomic imprinting since its discovery. In recent years, we have extensively invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
82
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 44 publications
2
82
0
2
Order By: Relevance
“…19,20 The imprinted, developmentally regulated lncRNA H19 is absent in most normal adult tissues; however, its reexpression has been detected in various cancers. [21][22][23] Since the discovery of H19 in 1984, 24 its function has remained enigmatic. Many studies using cell culture systems and mouse models have shown that H19 can function either as an oncogene [25][26][27] or a tumor suppressor.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 The imprinted, developmentally regulated lncRNA H19 is absent in most normal adult tissues; however, its reexpression has been detected in various cancers. [21][22][23] Since the discovery of H19 in 1984, 24 its function has remained enigmatic. Many studies using cell culture systems and mouse models have shown that H19 can function either as an oncogene [25][26][27] or a tumor suppressor.…”
Section: Introductionmentioning
confidence: 99%
“…The exact role of H19 in the maintenance of genomic stability and in the process of cellular transformation is unclear. However, previous studies showed that increased H19 expression levels can serve as a marker for tumor cells [21][22][23][24] , which lead to its use as a clinical bio-marker in the treatment of various cancer types [25] . In the recent work [20] it was unveiled that H19 expression is higher in proliferating cells, and is also elevated dramatically in cells exposed to UV light.…”
Section: Why Are Ascs More Gnomically Stable and Less Tumorigenic Thamentioning
confidence: 99%
“…Oncofetal H19 had been extensively investigated in cancer biology, even before research was focused on lncRNA (37,38). H19 is a paternally imprinted gene which locates at chromosome 11p15.5.…”
Section: Hox Antisense Intergenic Rna (Hotair)mentioning
confidence: 99%
“…H19 is highly expressed during embryonic development, but is repressed right after birth in most tissues (39,40). H19 is highly expressed during tumorigenesis and was shown to possess tumorigenic properties in all types of tissues (37,(41)(42)(43).…”
Section: Hox Antisense Intergenic Rna (Hotair)mentioning
confidence: 99%